Albert Camus – A Psychobiographical Approach in Times of Covid-19 - Mayer, Claude-Hélène (Frontiers in Psychology, 2021)
Albert Camus (1913–1960) stands as one of the famous pioneers in the French history of existentialism. He was a novelist, political activist, essayist and editor, as well as a journalist and playwright. Although he was described as philosopher, he often denied this ascription. Through his professional and creative expressions, Camus focused on questions of existentialism, the aspect of the human fate, and meaning in life, death and suicide. These existential questions have experienced a strong revival during the Covid-19 occurrence. This psychobiographical approach aims at understanding Albert Camus’ life and work in the context of the terror management theory of Ernest Becker and Wong’s four pillars of PP2.0 theory, namely virtue, meaning, resilience and well-being. Both theories have gained importance during the pandemic. Based on the findings of the research study, implications for future research in the context of the pandemic are given. Finally, this article provides recommendations and best practices on how to approach the Covid-19 pandemic from a terror management theory and PP2.0 perspective in the light of Albert Camus’ philosophy. The contribution of this psychobiography is twofold: first, it expands psychobiographical research on Albert Camus from absurdist and existentialist theories and thereby expands the theoretical framework of psychobiographies. Second, it aims at strengthening the importance of theoretical psychobiographical investigations and their application in real-world scenarios to address complex contemporary challenges on the basis of existentialist positive psychology theories.